Development of Timolol Maleate-Loaded Poloxamer-co-Poly (acrylic acid) based hydrogel for controlled drug delivery - Mansoor, Raneem; Barkat, Kashif; Anjum, Irfan; Aamir, Muhammad; Badshah, Syed Faisal; Ullah, Riaz; Iqbal, Zafar; Raza, Muhammad Ahmer (PloS one, 2024)
Free radical polymerization technique was used to formulate Poloxamer-188 based hydrogels for controlled delivery. A total of seven formulations were formulated with varying concentrations of polymer, monomer ad cross linker. In order to assess the structural properties of the formulated hydrogels, Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric analysis (TGA), Differential Scanning Calorimetry (DSC), Scanning electron microscopy (SEM), and X-ray diffraction (XRD) were carried out. To assess the effect of pH on the release of the drug from the polymeric system, drug release studies were carried in pH 1.2 and 7.4 and it was found that release of the drug was significant in pH 7.4 as compared to that of pH 1.2 which confirmed the pH responsiveness of the system. Different kinetic models were also applied to the drug release to evaluate the mechanism of the drug release from the system. To determine the safety and biocompatibility of the system, toxicity study was also carried out for which healthy rabbits were selected and formulated hydrogels were orally administered to the rabbits. The results obtained suggested that the formulated poloxamer-188 hydrogels are biocompatible with biological system and have the potential to serve as controlled drug delivery vehicles.
Keywords: Timolol; Acrylic Resins; spektroskopie infračervená s Fourierovou transformací; difrakce rentgenového záření; diferenciální skenovací kalorimetrie; Hydrogen-Ion Concentration; Calorimetry, Differential Scanning; Poloxamer; timolol; Hydrogels; Drug Liberation; Microscopy, Electron, Scanning; Thermogravimetry; lékové transportní systémy; Drug Delivery Systems; králíci; hydrogely; Delayed-Action Preparations; X-Ray Diffraction; poloxamer; uvolňování léčiv; léky s prodlouženým účinkem; mužské pohlaví; zvířata; Spectroscopy, Fourier Transform Infrared; nosiče léků; termogravimetrie; Animals; Rabbits; Male; koncentrace vodíkových iontů; mikroskopie elektronová rastrovací; akrylové pryskyřice; Drug Carriers